DISTRIBUTION AND DIVERSITY OF GASTROPODS (MOLLUSCS) IN INTERTIDAL WATERS IN RUPAT SUBDISTRICT, BENGKALIS DISTRICT - Pratama, Muhammad Dandy Syifa; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This study aims to determine the distribution pattern and diversity of gastropods in the Intertidal Waters of the Rupat Timur District. The research was conducted in February 2022. The research location consisted of 3 stations, each station was placed 3 transects from the highest tide to the lowest tide at different distances. Along the transect lines were placed 3 plots with a size of 3 x 3 m and each plot has a subplot with a size of 1 x 1 m. The method used in this research is the survey method. Parameters measured include gastropod species, distribution patterns, diversity, abundance, relative abundance, and water quality. The results of the study found gastropod species consisting of 9 (nine) families, 12 (twelve) genera, and 13 (thirteen) species. The distribution pattern of gastropods in the research location is clustered with the value of diversity (H') at a moderate level of diversity. Diversity is categorized as moderate. The highest abundance of gastropods was found on the beach of Sukarjo Mesim Village (a station I) with an abundance value of 25,600 ind/ha and the lowest abundance was found on the beach of Teluk Lecah Village (station III) with an abundance value of 11,100 ind/ha, while the highest abundance of gastropods between intertidal subzones was in the upper zone with an abundance value of 20,400 ind/ha and the lowest abundance was in the lower zone with an abundance value of 12,200 ind/ha. The highest relative abundance was Indothais javanica species with a relative abundance value of 18.30%, while the lowest relative abundance was Oliva ornata species with a relative abundance value of 0.85%. Temperature 29-30o C; salinity 28-30 ppt; pH 5-6; DO 5.2-6.4 mg/l. Sediment type in the station I was dominated by mud, station II was dominated by muddy sand and station III was dominated by sand with total sediment organic matter content of 0.46-23.33%.